Water balance dynamics in mixed crop-livestock systems of northern Ghana: Unraveling the interactions between farm-level and landscape fluxes in the face of climate change - Kizito, Fred; Panyan, E.K.; Ayantunde, Augustine A.; Bossio, Deborah A.; Karbo, N.; Avornyo, Franklin K.; Tengan, K. (Scientific Research Publishing, Inc., 2014)
Agro-ecosystem productivity is highly dependent on moisture fluxes yet climate variability and climate change induce unpredictable dynamic interactions between farm-level and landscape-level flow of water resources. In this study, water balance dynamics at the farm level were investigated using real-time in-situ data collected with automated data loggers while the Water-World model populated with long-term hydrological and climatic data was used to ascertain the impact of climate change on moisture fluxes at landscape level on agro-ecosystems of Northern Ghana. On-farm seasonal water balance estimates within intercropped maize-soybean stands revealed that with the 716 mm of rainfall receivedin the season, evapotranspiration (ET) was the predominant factor accounting for about 78% of the fluxes. We demonstrate that runoff levels were not significant for intercropped stands where farmers had conducted soil and water conservation measures which translated to 30% lower runoff levels compared to the control treatments. From a bioclimatic standpoint, study results indicate a steady increase in temperature and a projected increase in rainfall over the next 40 years to the 2050s. Increment in rainfall amount could be desirable considering the recurrent dry spells in the Northern parts of Ghana. However, the shorter term impacts, particularly changes in the frequency and severity of rainfall events remain uncertain since increased amounts over short durations may translate into regional extreme events and could increase runoff severity in an area that is already prone to flooding. We surmise that managing variability in terms of innovative water storage solutions that complement soil and water conservation measures will reduce runoff levels and erosion and also help farmers with better coping mechanisms and adaptation to climate change, particularly among the poor resource farmers in these vulnerable landscapes.